JUSTIFICATION OF THE EXECUTIVITY OF THE SINGLE-FORMAT TECHNOLOGY OF AUTOMATED PROCESSING OF THE RESULTS OF GEODESIC MEASUREMENTS: Array - Dorozhko, Y.; Zakharova, Е.; Sarkisian, G.; Mikhno, P. (Municipal economy of cities. Series: «Economy science», 2021)
The expediency of single-format technology of automated processing of geodetic measurements for the needs of the road construction industry is considered. This technology allows you to perform end-to-end automated processing of geodetic measurements with subsequent automated design and transfer the results of one design phase to the next in a single format and a single design environment. Through single-format automated technology for processing geodetic measurements and development of design solutions is to transfer the results of one stage of data processing or development of design solutions to another in one format and one software package. In the event of any corrections to previous results or the development of new solutions at any stage, all changes should be reflected in all parts of the project. This approach will allow the use of a one-time digitally developed highway project at all subsequent stages in the development of overhaul and reconstruction projects, subject to changes in the digital model of the area. The digital model of the terrain and section of the highway constructed in this way can be constantly adjusted and used at the stages of geodetic surveys, design, construction or repair and maintenance until the next geodetic surveys. End-to-end single-format cycle includes: design, technological design, engineering analysis, control programs. This ensures the integrity of the geometry in the transition to each subsequent stage. Providing end-to-end automated automated processing of geodetic measurement results for road repair or construction design tasks can be done by involving software products such as «CREDO», «Topomatic Robur», «Autodesk Civil 3D» and others. The use of single-format end-to-end automated processing of geodetic measurements with the subsequent construction of a digital terrain model will speed up and facilitate the development of design solutions, improve their quality, which in turn improves the quality of roads and man-made structures.